NILAI KARAKTER DALAM NOVEL MENCINTAI-NYA SEBELUM MENCINTAIMU KARYA RISKA WATI HARFIN - Rahmat Rahmat (EDU-KATA, 2021)
The purpose of this thesis research is to describe the character values ​​taught by Harfin in the novel Loving Him before Loving You. This study uses a qualitative method. Qualitative method as a research procedure that produces descriptive data in the form of words, phrases, clauses, and sentences for each paragraph. Research data are data sources, collection techniques and data analysis techniques which include data description, data analysis and data conclusions. Data analysis was carried out by content analysis to reveal the 5 character values, namely religious character, mutual cooperation, independence, nationalism and integrity. Religious characters have good characters (protagonists) and person who are ugly. Character of mutual cooperation is the attitude of helping and advising each other. The usual independent character lives in deprivation, hard work, has a motivation that is less dependent on others. Nationalism character in the form of dedication of honorary teachers in an elementary school. The integrity character of hard work with confidence and optimism can complete the work while praying to Him. The character implanted can be a reference for learning in schools in order to realize Indonesian children who are religious, mutual help, independent, nationalism and integrity.